PENGARUH TEKNIK STERILISASI EXPLAN TERHADAP TINGKAT PEROLEHAN KULTUR JARINGAN AKSENIK RAMIN (Gonystylus bancanus) - Asri Insiana Putri; Toni Herawan; Prastyono Prastyono; Liliek Haryjanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2017)
Since 2005, ramin has been included in CITES Appendix II and according to IUCN red list, ramin is also regarded as vulnerable (VU A1cd). The Lack of information on explant sterilization techniques in ramin tissue culture is one reason why there has not been enough initiation to develop ramin micro propagation. Plant tissue culture contamination has economic impact due to its direct influence in losses during in vitro culture of plants. The aim of this study was to observe the influence of explants sterilisation technique on acquisition rate of ramin axenic tissue culture with the rate of contamination increase, acsenic culture acquisition and shoot elongation as parameters. Ramin seedlings as explants source were collected from Tumbang Nusa, Central Kalimantan. Fifty replicating explants of one nodule each in 3 techniques were used in this study based on in vitro incubation time: sterilization 1 (24 hours incubation), sterilization 2 (48 hours incubation) and sterilization 3 (72 hours incubation) with non metallic antimicrobial compounds namely detergent, ditiocarbamate with mankozeb active ingredient (compound A), a compound containing 5.25% NaOCl added sodium hypochlorite and hydrogen oxide (compound B), 70% alcohol (compound C) as explants surface sterilants. Murashige-Skoog was used as media for evaluation of sterilization technique and explants regeneration on one year incubation. The results of this study indicate that the lowest rate of contamination was found in sterilization 3 (28%) with the success number of axenic tissue culture at 46%. The average shoot elongation of the axenic culture was 5.91 cm after 12 months subcultured in every month.